Phlebotominae Fauna (Diptera: Psychodidae) and the Spatial Distribution of Species in Sergipe, Brazil - Andrade, David Campos; de Assis Lima, Antônio Fernando Viana; de Lourdes Sierpe Jeraldo, Verónica; de Melo, Cláudia Moura; Pinto, Mara Cristina [UNESP]; Madi, Rubens Riscala (Oxford University Press (OUP), 2023)
Some sand fly species are the vectors responsible for the transmission of Leishmania spp. (Kinetoplastida: Trypanosomatidae), the etiological agent of leishmaniasis, and in the state of Sergipe, the two main forms of the disease (visceral and cutaneous) are recorded. Few works show information about the species that form the Phlebotominae fauna in Sergipe. This study aimed to update and determine how they are distributed throughout the state.The study used data from surveys about phlebotomines in Sergipe, from the Program of Surveillance and Control of Visceral Leishmaniasis, carried out by the Central Public Health Laboratory of Sergipe, from 2008 to 2018, along with review and original data from 2022.The commentary on this information was developed with focus on the species that can be vectors for the disease. Sergipe has, up to now, 27 registered species of phlebotomines from 12 genera, 15 of them are of sanitary relevance.Twenty two of these species are in the mesoregion East, 19 in the Agreste, and 11 in the Sertão of Sergipe.The species with the greatest distribution was Evandromyia lenti (Mangabeira, 1938), present in 74.6% of the municipalities of Sergipe, followed by Lutzomyia longipalpis (Lutz & Neiva, 1912), the main vector of the etiological agent of visceral leishmaniasis in Brazil, present in 68% of the municipalities studied.This study expands the number and distribution of species recorded in the state. This information can contribute to disease containment plans and support health education actions aimed at the control of leishmaniasis in Sergipe.
Keywords: diversity; Leishmaniasis; vector; vector control of diseases; visceral